Grumentum - Laes, Christian; Buonopane, Alfredo (Brepols, 2020)
About 130 Latin inscriptions shine a fascinating light on the medium-sized Roman town of Grumentum in ancient Lucania. Most of these stones have hardly been studied since the end of the 19th century. They now for the first time appear in a scholarly edition with revised Latin text, illustration, apparatus criticus, translation and extensive commentary. Both the introduction and the edition illustrate the richness of the material: archaeology, politics, institutions, the Roman army, economy, religion, family and life course, and Christianity are dealt with. The use learned scholars made of the inscriptions opens a window to Italian intellectual history from the Renaissance on. Written and presented in an accessible way, this volume avoids the pitfalls of highly technical epigraphical editions, and opens the field to archaeologists, (ancient) historians and a more general audience with an interest for Roman sites in general, and this hidden gem in Basilicata in particular.